A Raman, SERS and UV-circular dichroism spectroscopic study of: N-acetyl-l-cysteine in aqueous solutions - Picot, R. A. Cobos; Puiatti, M.; Ben Altabef, A.; Rubira, R. J.G. [UNESP]; Sanchez-Cortes, S.; Diaz, S. B.; Tuttolomondo, M. E. (Royal Society of Chemistry (RSC), 2019)
The aim of this work is to evaluate the vibrational and structural properties of N-acetyl-l-cysteine (NAC), and its molecular structure and electronic properties in relation to the action of thiol and amine groups at different pH. Raman and Surface Enhanced Raman Spectroscopy (SERS) spectra were measured in aqueous solution. The influence of an aqueous environment on the NAC spectra was simulated by means of an implicit (polarizable continuum model) method. SERS spectra indicate that the S atom is interacting with the surface through the sulfur atom. One of the consequences of the interaction with the surface is the deprotonation of the SH group, as revealed by the disappearance of the ν(S-H) band. The calculations performed for the Ag-NAC complex confirm the experimental data obtained by SERS, where the S-Ag interaction is the most important. These results are very interesting when one can formulate the drug feasibility of NAC using silver nanoparticles as a carrier. Raman spectra were measured to compare the behavior of different functional groups in the molecule, both in the solid phase and in aqueous solution at different pH. Apparent ionization constants (pK′ values) for the S-H group at high ionic strengths were calculated from the intensity of the 2580 cm-1 frequency as a function of pH. UV and circular dichroism spectra were also measured in aqueous solution at different pH. Finally, the study was completed with natural bond orbital (NBO) analysis to determine the presence of hyper-conjugative interactions. It is important to observe the behavior of the C2-N bond with the delocalization effect; as the pH increases the hyperconjugative interaction of this bond decreases in the same way as in the case of νCN. The way in which the LP πO1 → σ∗C2-N interaction and νCN decrease is an inverse reflection of the fractional ionization αSH.